Physiological disorders in perennial woody tropical and subtropical fruit crops: A review - RAJESH KUMAR; VINOD KUMAR (The Indian Journal of Agricultural Sciences, 2016)
The productivity as well as the quality of fruit crops is affected to a greater extent due to various physiological disorders. The extremes of environmental variables like temperature, moisture, light, aeration and nutritional imbalances result in disturbances in the plant metabolic activities leading to these disorders. While the symptoms may appear disease-like, they can usually be prevented by altering environmental conditions. In fruit crops, the deficiency of micronutrients causes many more disorders than that of macronutrients. These disorders have become widespread with diminishing use of organic manures, adoption of high density planting, use of rootstocks for dwarfing, disease and salt tolerance, unbalanced NPK fertilizer application and extension of horticulture to marginal lands. To get high quality fruit and yields, micronutrient deficiencies have to be detected before visual symptoms are expressed. This article presents a critical review on cause and characteristics of physiological disorders in important woody perennial fruit crops, viz. mango, litchi, guava, citrus, aonla, pomegranate, sapota, cashew, coconut, bael, ber and jackfruit, besides providing an insight into the gaps and researchable issues. The critical analysis of the nature, origin and causative factors of these non-pathogenic disorders will help in formulation of management strategies, reducing the loss to a significant level.